Analysis of Public Satisfaction Index in Kedungadem Public Health Center: Evaluation of Service Quality in Semester II, 2024 - Rahmawati, Dwi Yana; Siswati, Ayu; Mujanah, Siti; Alifianto, Achmad Yanu (Jurnal Manajemen dan Inovasi (MANOVA), 2025)
Objective – This study aims to evaluate the quality of public services and obtaim feedback on the performance of services provided to the community for continuous improvement of service performance based on the Public Satisfaction Index (IKM) at the Kedungadem Health Center in Semester II of 2024. Methodology – This research uses a quantitative descriptive approach through surveys to 100 respondents each from 14 villages and 13 types of health services. The score was measured using data processing techniques for analyzing the IKM. The survey instrument uses a questionnaire that is compiled based on 9 service elements determined by govemment regulations. Findings – The overall IKM value of the Kedungadem Health Center service is 85.40. which is categorized in the "Good" category. However, the element of Handling Complaints with a value of 66.55 and Product Specifications of Service Types, especially toilet cleanliness with a value of 72.45 in the "'Not Good" category so that it still needs to be improved. Research limitations/implications – This study was only conducted in one health center and only covered a period of one semester. Practical implications – The results can be used as evaluation material for health service managers in improving service quality in certain aspects. Originality/value – This research presents the practical application of IKM in evaluating and improving public services in the health sector, especially in health centers.